PERADILAN SADDAM HUSSEIN: HEGEMONI AMERIKA DAN TRAGEDI GOOD WORLD GOVERNANCE - Faiz Tajul Millah (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2007)
After the destroying of World Trade Center USA on September 11 2001, America is focusing his international political policy on war on terrorism which was further followed by preemptive action and unilateralism toward countries considered a terrorist. One of them is Irak. Certainly the policy will hamper the realization of good world governance under the United Nations Program. Attacking Irak in 2003 is a real proof of the USA hegemony in the world as the Super Power, especially concerning about Saddam Husein’s process of judicature which is hold by Iraqi Special Tribunal and the Iraqi Special Tribunal is under the US intervention. Teoritically the session process of Saddam who was accused executing genocide toward Kurdi tribe should be hold by International Criminal Court (ICC) under the United Nations. It is not the competency of Iraqi Special Tribunal. The session Process of Saddam judicature is considered invalid and breaking out the principals of international law. This case will hamper the maintenance of international law supremacy. The maintenance of international law is one of the requirements of good world governance. However, the reality is showing that international politic under USA hegemony, and this will always hamper the realization of good world governance.